The evolution of debtor-creditor relationships within a monetary union: Trade imbalances, excess reserves and economic policy - Claudius Gräbner; Philipp Heimberger; Jakob Kapeller; Michael Landesmann; Bernhard Schütz (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2021)
This paper analyses the emergence of internal debtor-creditor relationships within a monetary union. Developing a stock-flow consistent model consisting of three regions - North, South, and the Rest of the World (RoW), where North and South form a monetary union - it shows how the simultaneous presence of investment booms, declining export performance and mercantilist policies within a monetary union can interact in order to create Minsky-type boom-bust cycles. Fiscal policy and an internal lender of last resort can help sustain economic life under existing structural imbalances, though without eliminating the root causes of boom-bust patterns.
Keywords: E12; F41; F45; G01; G18; 330; Gläubiger; Kredittilgung; Finanzpolitik; Währungsunion; Nord-Süd-Beziehungen; Welt